Agresividad fiscal y rendimiento de las empresas que cotizan en bolsa en Brasil: Un análisis del período pandémico - Dantas Cerqueira, Amanda (2025)
The objective of this research was to investigate the influence of tax aggressiveness on the performance of companies listed on the Brazilian stock exchange (B3) during the pandemic period, spanning from 2017 to 2022, totaling 1,422 observations. Previous studies indicate that companies adopt tax planning strategies, such as tax aggressiveness, to improve financial reporting, a practice that intensified during the pandemic period between 2020 and 2022 (Costa et al., 2018; Esnolde et al., 2009). Data were collected from the Economatica® database and analyzed using multiple linear regression. Performance proxies included the return on assets (ROA) and return on equity (ROE) variables, while tax aggressiveness was measured using a combination of book-tax differences (BTD) and the effective tax rate (ETR) variables. The results showed that more tax-aggressive companies had superior performance throughout the entire analysis period, although no marginal positive effect was identified during the pandemic. Less aggressive companies did not experience significant performance losses before the pandemic, but there was a decline in their ROE during the pandemic period. These findings suggest a non-linear effect of the benefits of tax aggressiveness on performance, especially in crisis, because changes in the independent variables of tax aggressiveness did not result in a constant change in the dependent variable ROE during the pandemic.